PENGARUH DANA DESA DAN ALOKASI DANA DESA TERHADAP KEMISKINAN DI KABUPATEN PELALAWAN - Novrianti Novrianti; Dahlan Tampubolon; Mardiana Mardiana (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
This study aims to analyze how much influence the Village Fund and Village Fund Allocation (ADD) have on the number of poor people in Pelalawan Regency. The analytical tool used is multiple regression with panel data which is then tested for hypotheses with the F test, t test, and Coefficient of Determination (Adjusted R2) at an error rate of = 5%. The results of panel data regression analysis with the selected model is the Fixed Effect Model showing that there is an influence of the Village Fund and Village Fund Allocation (ADD) on the number of poor people in Pelalawan Regency from 2016-2020 with a value of 0.0000005 each for the Village Fund and -0.000000611 for ADD. While the value of Coefficient of Determination (Adjusted R2) is 0.8378 or 83.78%, this shows that the ability of the Village Fund and ADD variables in explaining rural poverty is 83.78%.